Desain Mesin Gergaji Portable Untuk Pembuat Kayu Gergajian Dari Batang Kelapa Sawit Dengan Pendekatan Design For Manufacture And Assembly (DFMA) - Handri Gustiar; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Oil palm trees wood are no longer productive after 25 year old, and will be cut down in the form of wooden logs. Wooden logs of oil palm are left piled on the land and into the waste oil palm trunk, so the need for a study on the design of the portable sawing machine to cultivate oil palm logs into sawn timber. This study aimed to obtain design parameters, the design of the portable chainsaw, and the application of appropriate technology. The method used in this study is that, in the selection of the design can be obtained by using software engineering drawings and researchers will choose a design with DFMA methods. The design process is conducted in 5 stages by identifying design flaws and fix them to get the best design, after the design is obtained then calculated the total assembly time using a table of manual handling time, and table of manual insertiontime is calculated, and the efficiency of assembly is also calculated. Results from this study is a final design sawing machinesawn timbermaker of portable oil palm trunks which has 2 working principle is to use thrustforce and using crank torque as the driving force. The total value is 295,2 seconds assembly time and the efficiency of the assembly 4,06%. It can be concluded that the design obtained has an easy manufacturing and assembling process.Keywords: DFMA, Total Assembly Time, Assembly Efficiency.